ANALISIS KINERJA MESIN PRESS PROGRESSIVE MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS PADA PERUSAHAAN METAL STAMPING - Rifa'i, Muhammad Rizal; Wahyudin, Wahyudin; Aldiansyah, Muhammad Reza; Sutrisno, Sutrisno (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2023)
The problem that is commonly found in manufacturing companies is how to carry out the production process effectively and efficiently. Especially doing maintenance on machines to get optimal production results. The P1-29 machine is one of the machines from a metal stamping company that produces automotive parts with stamping as the main process. The P1-29 machine is often unusable for the production process due to downtime. This study aims to determine factors that can cause downtime on the P1-29 machine in order to reduce the downtime. Therefore, an appropriate concept is needed to identify the performance of the production process with optimal effectiveness, efficiency and reducing the downtime. This appropriate concept is called by the Overall Equipment Effectiveness (OEE) method assisted by Pareto diagrams, fishbone diagrams, also kaizen five-m checklist and 5W + 1H analysis. The OEE value of the P1-29 engine for the period January-March 2022 is 62%. From this value, it can be seen that the OEE level does not meet the standards set by JIPM, which is >85%. The factors causing downtime on the P1-29 machine consist of various factors from the six big losses with the highest factor being the setup and adjustment losses of 17.47%. From the results of the fishbone diagram analysis, the factors that lead to the high value of setup and adjustment losses consist of human, material, machine, method and environmental aspects.